Population dynamics of Acanthospermum hispidum DC. under soil and herbicide management practices - Voll, Elemar; Gazziero, Dionísio L. P.; Karam, Décio (Pesquisa Agropecuaria Brasileira, 1997)
One experiment was carried out in the field, in Londrina, PR, Brazil on a duski latosol dystrophic, with 75% of clay and 2.7% of organic matter. The objective of this work was to determine the survival period and emergence rates of seeds of Acanthospermum hispidum DC. for predictive management uses in weed control. Soil management practices such as conventional tillage, moldboard tillage, scarification and heavy disc and no-till; postemergence herbicide management practices, present or not in soybeans, followed by wheat, were established during five years. Acanthospermum hispidum estimated survival periods for soil management practices, with herbicides or Brachiaria plantaginea (Link.) Hitch. competition, were of 10.9 years on average. Seed bank annual decreasing rate was about 37.0%. Emergence rates changed with year and soil management practices; the lowest rate was observed in no-tillage. Maximum emergence rate was of 1.0%, before soybean sowing; after sowing, emergence rates were between 0.6% and 6.5%. Seeds initial vertical distribution in soil was of no importance for management practices.
Keywords: no-till; weed control; survival; emergence